Use of the temporal extension of the buccal fat pad for closure of oro-antral communications. Issue 12 (December 2021) - Rathod, N.; Khobaragade, B.; Ganesan, K.
Abstract: Oro-antral communications/fistulae (OAC/OAF) can cause significant patient morbidity, with treatment for defects greater than 5 mm in size requiring surgical reconstruction. This technical note evaluates the effectiveness, and proposes the use of, the temporal extension of the buccal fat pad (TEBFP) for the closure of large OAC. The TEBFP can be an effective means of large OAC closure due to its ease of harvesting, with minimal damage to surrounding structures or aesthetic changes. The use of the TEBFP provides stability, versatility, and tension-free closure, with minimal postoperative complications.